The effect of enteral nutritional support and growth hormone on critical patients - Zhou, Rui-Xiang (Zhongguo wei zhong bing ji jiu yi xue = Chinese critical care medicine = Zhongguo weizhongbing jijiuyixue, 2010)
OBJECTIVE: To explore the effect of early enteral nutritional support and growth hormone (GH) on critical patients